2021
DOI: 10.3390/ijerph181910517
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression and Anxiety in Patients with Chronic Kidney Disease and after Kidney Transplantation—A Comparative Analysis

Abstract: Depression and anxiety are common among chronic kidney disease (CKD) patients but are rarely diagnosed and treated. Furthermore, the fraction of patients with depression is greater among hemodialyzed patients. The aim of the study was to assess the prevalence of depression symptoms, anxiety and assess the level of life satisfaction in three groups of patients based on the stage of CKD. The study group consisted of 283 patients—130 females and 153 males, mean aged was 54.7 (±15.3) with stage III–V chronic kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…This could suggest that non-MS HD patients benefit more in terms of reducing the severity of trait anxiety (X2) compared to patients with metabolic syndrome. This may be clinically relevant because, as shown in other studies [64], trait anxiety (X2) is most strongly associated with depressive symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…This could suggest that non-MS HD patients benefit more in terms of reducing the severity of trait anxiety (X2) compared to patients with metabolic syndrome. This may be clinically relevant because, as shown in other studies [64], trait anxiety (X2) is most strongly associated with depressive symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…Tsai et al, Lee et al, and Danielle et al reported clinical depression levels of 37% [ 59 ], 47.1% [ 60 ], and 40% [ 61 ], respectively, for CKD Stages III, IV, and V. Generally, patients with CKD (Stage V) displayed the highest prevalence of clinical depression [ 55 ]; however, this finding was inconsistent. Dziubek et al revealed a 53% prevalence of depression among patients with Stage V renal failure [ 62 ]. In this study, high levels of depression were not surprising because of the lack of quality support (financial, social, and medical), also reported by Hettiarachchi and Abeysena [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 The diagnose of depression in ESRD patients is challenging due to the overlap of the main somatic symptoms of the depression, such as anorexia, fatigue and sleep disturbances, with those of ESRD, 12 , 13 leading to delays in diagnosis and treatment. 14 Early and appropriate diagnosis of depression in ESRD patients is crucial for improving treatment adherence and quality of life. 14 , 15 Therefore, health care professional caring for HD patients should be qualified to regularly assess and investigate depression, facilitating promptly referral to psychologists for early treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Early and appropriate diagnosis of depression in ESRD patients is crucial for improving treatment adherence and quality of life. 14 , 15 Therefore, health care professional caring for HD patients should be qualified to regularly assess and investigate depression, facilitating promptly referral to psychologists for early treatment. 3 , 5 Recent studies highlight the positive impact of early nursing screening, psychological support, and nursing intervention in the treatment compliance, quality of life, and the reduction of anxiety, depression and risk of complications.…”
Section: Introductionmentioning
confidence: 99%